Reporting the Oregon Story : How Activists and Visionaries Transformed a State - McKay, Floyd J. (Book collections on Project MUSE., 2016)
"Oregon entered a new era in 1964 with the election of Tom McCall as Secretary of State and Bob Straub as State Treasurer. Their political rivalry formed the backdrop for two of Oregon's most transformative decades. Veteran Oregon journalist Floyd McKay had a front-row seat"--